The Role of Educational Communication by Teachers in Enhancing Pupil Engagement in Learning at SMPN 2 Doplang, Blora Regency - Yoga Adhitya Fredy Firmansyah; Muhamad Ilham; Livie Izzati Hasanah; Adhiswar Azizi (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
This study examines the role of educators' educational communication in increasing student engagement in teaching at Doplang State Junior High School 2 in Blora. Effective interaction is a key factor in establishing good relationships between educators and students through reciprocal communication and the use of participatory teaching methods. The research employed a descriptive approach with observation, interviews, and recording techniques for educators and students. The research findings demonstrate that educators' ability to explain teaching materials, provide feedback, and create a conducive learning environment can stimulate student participation. Methods such as stimulating questions, discussions, and awarding extra points have proven effective in increasing student engagement. However, student participation remains reactive and not fully independent. Differences in competency and self-confidence also influence participation levels. This research contributes to the development of more interactive and participatory communication strategies to maximize student engagement in learning. The findings also emphasize the importance of school support and parental involvement for a more effective and sustainable learning process.